2009
DOI: 10.1111/j.1600-0722.2009.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

The cholinesterase inhibitor physostigmine for the local treatment of dry mouth: a randomized study

Abstract: Application of physostigmine to the oromucosal surface with the aim of stimulating underlying mucin-producing glands while reducing cholinergic systemic effects might be a strategy for treating dry mouth. Subjects suffering from dry mouth and with hyposalivation participated in a crossover, double-blind, randomized study. A gel containing physostigmine (0.9, 1.8, 3.6, and 7.2 mg) or placebo was applied to the inside of the lips and distributed with the tongue. The feeling of dryness was assessed using a visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…This phenomenon has also been reported in several previous studies [1, 11, 31, 42]. It has been suggested that the menopause and female hormone oestrogen are influencing the salivary function in common with many other physiological and psychological functions.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This phenomenon has also been reported in several previous studies [1, 11, 31, 42]. It has been suggested that the menopause and female hormone oestrogen are influencing the salivary function in common with many other physiological and psychological functions.…”
Section: Discussionsupporting
confidence: 84%
“…Also gustatory and mechanical salivary stimulating techniques may be helpful to relieve the feelings of xerostomia, such as consuming sugar-free chewing gum, candies, and mints, as well as acidic drinks and foods [30, 45]. Systemic medication of pilocarpine or cevimeline or application of physostigmine to the oral mucosal surface may improve saliva secretion, but the possible side effects should be determined and, if possible, anticipated or controlled [42, 46, 47]. When stimulating salivary secretion is not possible or not adequate, symptomatic relief of the oral complaints becomes the primary management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Further research should focus on other symptom‐relieving systems, such as intraoral relieving devices or containers and new methods with focus on the underlying reasons for xerostomia. Promising and innovative methods have been presented over recent years (Alajbeg et al, ; Khosravani, Birkhed, & Ekstrom, ; Strietzel et al, ). Due to their relatively short time span of symptom relief, it remains questionable whether the mouth gels investigated in our study should be used for whole‐day symptom relief; instead, they could be used for short‐term relief of symptoms in planned situations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Sialometry results can be parsimoniously explained by the summation of two opposing effects: decreased salivation during stress and increased salivation following ChE inhibition (Hugo et al, 2008;Khosravani et al, 2009). The stress associated with the study induced decreased salivation, as is evident in the placebo group, and this was counteracted by rivastigmine.…”
Section: Discussionmentioning
confidence: 83%